2017
DOI: 10.3390/s17050982
|View full text |Cite
|
Sign up to set email alerts
|

Chemiresistor Devices for Chemical Warfare Agent Detection Based on Polymer Wrapped Single-Walled Carbon Nanotubes

Abstract: Chemical warfare agents (CWA) continue to present a threat to civilian populations and military personnel in operational areas all over the world. Reliable measurements of CWAs are critical to contamination detection, avoidance, and remediation. The current deployed systems in United States and foreign militaries, as well as those in the private sector offer accurate detection of CWAs, but are still limited by size, portability and fabrication cost. Herein, we report a chemiresistive CWA sensor using single-wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 59 publications
(66 reference statements)
1
44
0
2
Order By: Relevance
“…105 Swager and co-workers showed that conjugated polymers attached to selector side chains can provide selectively for the detection specific analytes and even resolve very similar structural isomers. 47,73,97,106,107 CNTs can also be functionalized with polymeric surfactants containing long alkyl chains that interact via hydrophobic interactions. 108,109 Dai and co-workers demonstrated the adsorption of Tween 20 conjugates containing biotin, staphylococcal protein A (SpA), or human autoantigen U1A to CNTs.…”
Section: Introduction and Scopementioning
confidence: 99%
“…105 Swager and co-workers showed that conjugated polymers attached to selector side chains can provide selectively for the detection specific analytes and even resolve very similar structural isomers. 47,73,97,106,107 CNTs can also be functionalized with polymeric surfactants containing long alkyl chains that interact via hydrophobic interactions. 108,109 Dai and co-workers demonstrated the adsorption of Tween 20 conjugates containing biotin, staphylococcal protein A (SpA), or human autoantigen U1A to CNTs.…”
Section: Introduction and Scopementioning
confidence: 99%
“…gas molecules [9]. In gas sensing applications, SWCNTs have been demonstrated for the detection of common organic vapors, [10] oxidizing vapors such as Cl2 or NO2, [11] and even trinitrotoluene (TNT) [12] and chemical warfare agents [13]. The main drawbacks for the application of SWCNT in sensors are the high price and the necessity to find techniques to deposit them on the active area of a resistive sensor with high enough conductivity [14].…”
Section: Introductionmentioning
confidence: 99%
“…Functionalizing CNTs with conjugated polymers for sensor applications has appeared in the field of gas sensing, 14,41 drug delivery, 42 chemical sensing 9,31,32,43,44 or biosensing. 45,46 If many articles have adressed the question of selective non-covalent functionalization of SWNTs (with diameter of order 0.7 to 1.5 nm) by conjugated polymers, and in particular polyfluorene derivatives, 28,29,47 the features of MWNTs (or very large diameter CNTs) and polyfluorene hybrids have not been investigated yet by simulation techniques.…”
Section: Introductionmentioning
confidence: 99%